The Effect of Comparison of Polypropylene Plastic Waste Composition and Paper Sludge On Fiber Reinforced Composite Panels of Sugarcane Bags on Mechanical Properties - Ismathul Dinny; Yenni Darvina (Department of Physics – Universitas Negeri Padang UNP, 2022)
Indonesia's landfills contain 15% of plastic waste. Of the total plastic waste, some are recycled and stored in the TPA. The remaining unmanaged will be wasted into the environment. Therefore, it is necessary to utilize waste so that it does not damage the environment, for example the use of waste into composite boards. Composite board made from polypropylene plastic wastepaper sludge and bagasse fiber. This study aims to see the effect of the composition of polypropylene plastic waste and the effect of paper sludge composition on the mechanical properties of composite panels. Composites are made using the hand lay-up method. The compositions used varied, namely 60% polypropylene plastic waste: 40% paper sludge, 50% polypropylene plastic waste: 50% paper sludge, 40% polypropylene plastic waste: 60% paper sludge with 2% bagasse fiber. Based on the results of research on the composition of polypropylene plastic waste of 60% and paper sludge composition of 40%, the highest tensile strength, compressive strength and hardness values were 11.86 N/mm2, 21.54 MPa and 6.33 HV. And the composition of plastic waste polypropylene by 40% and composition of paper sludge by 60% obtained the lowest tensile strength, compressive strength and hardness of 1.23 N/mm2, 9.77 MPa and 4.53 HV. From this study, it can be concluded that if the composition of polypropylene plastic waste is used more and more and the composition of paper sludge used is less, the value of mechanical properties will be higher. The value of the mechanical properties produced has met SNI